Robotic surgery can be safely performed for patients and healthcare workers during COVID‐19 pandemic. Issue 4 (3rd June 2021) - Sparwasser, Peter; Brandt, Maximillian P.; Haack, Maximillian; Dotzauer, Robert; Boehm, Katharina; Gheith, Mohammed Kamal; Mager, Rene; Jäger, Wolfgang; Ziebart, Alexander; Höfner, Thomas; Tsaur, Igor; Haferkamp, Axel; et al.
Abstract: Objectives: To investigate the safety of robotic surgery during COVID‐19 pandemic concerning new‐acquired COVID‐19 infections for patients and healthcare workers. Patients: We performed a retrospective single‐centre cohort study of patients undergoing robotic surgery in initial period of COVID‐19 pandemic. Patients and healthcare workers COVID‐19 infection status was assessed by structured telephone follow‐up and/or repeated nasopharyngeal swabs. Results: After 61 robotic surgeries (93, 5% cancer surgery), one patient (1.6%) had COVID‐19 infection. Sixty healthcare workers cumulatively exposed to 1187 h of robotic surgery had no infection. One patient with postoperative proof of SARS‐CoV‐2 had complete recovery. After this potentially contagious robotic surgery, eight healthcare workers had no COVID‐19 infection after follow‐up with each three nasopharyngeal swabs. Conclusions: Early clinical experience of robotic surgery during COVID‐19 pandemic shows that robotic surgery can be safely performed for patients and healthcare workers. Despite our results we recommend elective surgery only for verified COVID‐19 negative patients.